2010
DOI: 10.1038/ni.1908
|View full text |Cite
|
Sign up to set email alerts
|

Integrin CD11b negatively regulates TLR-triggered inflammatory responses by activating Syk and promoting degradation of MyD88 and TRIF via Cbl-b

Abstract: Integrins are critical for the migration and function of leukocytes in inflammation. However, the interaction between integrin alpha(M) (CD11b), which has high expression in monocytes and macrophages, and Toll-like receptor (TLR)-triggered innate immunity remains unclear. Here we report that CD11b deficiency enhanced TLR-mediated responses in macrophages, rendering mice more susceptible to endotoxin shock and Escherichia coli-caused sepsis. CD11b was activated by TLR-triggered phosphatidylinositol 3-OH kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
454
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(485 citation statements)
references
References 45 publications
24
454
2
5
Order By: Relevance
“…CD11b is widely expressed in DCs, NK cells, macrophages, and activated CTLs. Our study showed that CD11b on macrophages could be activated by the TLR4 signal via TLRtriggered PI3K and the effector RapL, and feedback negatively inhibited TLR4 signaling (15). In addition, CD11b expression also increases rapidly in NK cells upon TLR3 ligand stimulation, and, in turn, negatively regulates NK cell activation (16).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…CD11b is widely expressed in DCs, NK cells, macrophages, and activated CTLs. Our study showed that CD11b on macrophages could be activated by the TLR4 signal via TLRtriggered PI3K and the effector RapL, and feedback negatively inhibited TLR4 signaling (15). In addition, CD11b expression also increases rapidly in NK cells upon TLR3 ligand stimulation, and, in turn, negatively regulates NK cell activation (16).…”
Section: Discussionmentioning
confidence: 82%
“…CD11b-deficient mice (B6.129S4-Itgam tm1Myd /J; 003991) and OT-I mice (C57BL/6-Tg(TcraTcrb)1100Mjb/ J;003831) were described previously (8,15,16). All animal experiments were undertaken in accordance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals, with the approval of the Scientific Investigation Board of the Second Military Medical University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, integrin aMb 2 is crucial for effective FcR-mediated immunity to melanoma (53) and promotes the survival of mouse NK cells (54). In addition, it inhibits TLR-triggered inflammatory responses and prevents excessive production of proinflammatory cytokines and type I IFN (55). Recent research has highlighted a critical role for inflammation in the development of cancers, based on the observation that innate immune cells drive tumor progression by producing proinflammatory factors such as TNF-a and IL-6 (56-58).…”
Section: Discussionmentioning
confidence: 99%
“…), Nodlike family proteins (NLRX1, NLRC5, 18,19 etc. ), membrane molecules (CD300F, CD11b, PECAM-1, 20,21 etc. ), endosome/lysosome-localized molecules (Rab7b, 22,23 CLM-3 24 ), gene transcription coactivators (beta-catenin 25 ), antigen-presenting molecules (MHC I and MHC II 26,27 ), and even HSP70, 28 HSP70L1 29 and NGF.…”
Section: Introductionmentioning
confidence: 99%